2007
DOI: 10.1080/07420520701649455
|View full text |Cite
|
Sign up to set email alerts
|

Phase Advance Is an Actimetric Correlate of Antidepressant Response to Sleep Deprivation and Light Therapy in Bipolar Depression

Abstract: The combination of total sleep deprivation (TSD) and light therapy (LT) in bipolar depression causes rapid antidepressant effects, and its mechanism of action has been hypothesized to involve the enhancement of all of the monoaminergic systems targeted by antidepressant drugs (serotonin, dopamine, norepinephrine). It is still unknown if the clinical effects are paralleled by changes in biological rhythms. In a before/after design of a study of biological correlates of response, 39 inpatients affected by Type I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(47 citation statements)
references
References 60 publications
3
44
0
Order By: Relevance
“…More severe depression was associated with later circadian oscillators about the onset of sleep. It is interesting that a phase advance in actimetric parameters correlates with an antidepressant response in bipolar patients to chronotherapeutic interventions (Benedetti et al, 2007). Similarly, in the present study, the ARMS group began their M10 (the most active 10 h of the day) later, showing a gap between sleep onset.…”
Section: Discussionmentioning
confidence: 93%
“…More severe depression was associated with later circadian oscillators about the onset of sleep. It is interesting that a phase advance in actimetric parameters correlates with an antidepressant response in bipolar patients to chronotherapeutic interventions (Benedetti et al, 2007). Similarly, in the present study, the ARMS group began their M10 (the most active 10 h of the day) later, showing a gap between sleep onset.…”
Section: Discussionmentioning
confidence: 93%
“…In reported trials, recovery sleep is free and undisturbed, with the patient choosing the most appropriate bedtime and waking up when the night sleep ends spontaneously. Actigraphic evidence showed that after total SD patients significantly anticipate bedtime and sleep onset, and sleep more and better than before treatment (when sleep was usually disturbed by depressive insomnia) [52] .…”
Section: Recovery Sleep and Relapsementioning
confidence: 99%
“…Our group developed a treatment schedule based on repeated total SD, three times a week, resulting in a lengthening of the sleep-wake period from the usual 24 to 48 h [1, [45][46][47][48][49][50][51][52] . Each SD cycle is composed of a period of 36 h awake, and on the 1st, 3rd and 5th day, patients are totally sleep deprived from 07: 00 h until 19.00 h of the following day.…”
Section: Repetiton Of Treatmentmentioning
confidence: 99%
“…A recent study has shown that when total sleep deprivation and light therapy advance phase of activity-rest rhythms in bipolar depression patients, the degree of depression is significantly reduced/improved (Benedetti et al, 2007). Phase advancing effects of these two therapies support the significant relations between circadian rhythm generations and regulation of mood.…”
Section: Discussionmentioning
confidence: 99%